Analisis Pengaruh Branding Visual terhadap Minat Beli Konsumen - Januar Ibrahim; Olivia Dolorosa Tambunan; Abdul Husenudin (MES Bogor, 2025)
This study aims to determine the influence of visual branding on consumer buying interest among students of University X. The research method used is a quantitative method with 100 respondents selected by random sampling. Data was collected through a questionnaire using a Likert scale and analyzed with the help of SPSS software and Smart PLS 4 software. The results of this study show that visual branding has a significant influence on the buying interest of State University X students, that 55% of students' buying interest is influenced by visual branding, which includes design elements such as logos, colors, and typography. Visual branding plays an important role in creating a strong image and building consumer trust, which ultimately improves purchasing decisions. Therefore, it is important for companies to pay attention to visual branding elements in their marketing strategies to create a more immersive and memorable consumer experience.